Análise crítica da contribuição da Semana Nacional de Ciência e Tecnologia para a popularização do conhecimento científico - Sousa, Felipe Conrado Fiani Felipe de [UNESP] (2015)
The National Week of Science and Technology has been held since 2004 as one of the main initiatives of the Ministry of Science, Technology and Innovation for the popularization os scientific knowledge in the country, combiniting efforts of the areas of formal and non-formal education. This study characterized the contribution of the 2013 SNCT to the popularization of scientific knowledge to the general public. The specific goals were: a) to investigate principles, guidelines and lines of action of popularization activities of scientific knowledage currently adopted in Brazil and in the European Union, in comparative perspective; b) to investigate the contextualization of science popularization of activities carried out during the National Week of Science and Technology in the State of São Paulo in 2013, in relation to references to social and environmental impacts of technological applicatons and the social conditions of production of scientific knowledge, as the relationship between social actors (government, industry, universities and funding agencies) and the formulation of research priorities; c) to propose practical recommendations for conducting activities of popularization of scientific knowledge in the National Week of Science and Technology that contribute to tue public understanding of science and technology in the context of their social conditions of production and social and environmental impacts. The results suggest that there is a limited reference (4,9%) to the social impacts of science and technology in the analyzed activities. The coordinators surveyed recognize the importance of a broader context in relation to the social conditions of production of science and its environmental impacts, but factors such as lak of planning and material and human resources limited their approaches